2020
DOI: 10.2139/ssrn.3765310
|View full text |Cite
|
Sign up to set email alerts
|

Trade Protection Along Supply Chains

Abstract: During the last decades, the United States has applied increasingly high trade protection against China. We combine detailed information on US antidumping (AD) duties-the most widely used trade barrier -with US input-output data to study the effects of trade protection along supply chains. To deal with endogeneity concerns, we propose a new instrument for AD protection, which combines exogenous variation in the political importance of industries with their historical experience in AD proceedings. We find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 65 publications
(123 reference statements)
0
12
0
Order By: Relevance
“…Different from anti-subsidy or anti-dumping measures, safeguards do not require unfair trade practices of the exporting countries.69 Jabbour et al (2019) andBown et al (2020) show that the more widely used anti-dumping tariffs, which are justified by other countries' unfair pricing practices, had no positive aggregate effects on employment in France and the US, respectively. Such tariffs did little to shore up domestic employment in protected industries, but were associated with job losses and lower wages in downstream customer industries.70 The MFA, which was originally instituted in 1974, was gradually phased out from 1995 to 2005.…”
mentioning
confidence: 99%
“…Different from anti-subsidy or anti-dumping measures, safeguards do not require unfair trade practices of the exporting countries.69 Jabbour et al (2019) andBown et al (2020) show that the more widely used anti-dumping tariffs, which are justified by other countries' unfair pricing practices, had no positive aggregate effects on employment in France and the US, respectively. Such tariffs did little to shore up domestic employment in protected industries, but were associated with job losses and lower wages in downstream customer industries.70 The MFA, which was originally instituted in 1974, was gradually phased out from 1995 to 2005.…”
mentioning
confidence: 99%
“…Prusa (1997), Bown and Crowley (2006), Bown and Crowley (2007), Baylis and Perloff (2010), and find that AD tariffs increase imports from non-targeted countries, while Konings et al (2001) and Durling and Prusa (2006) do not find a significant third-country effect. This literature has also found that AD tariffs affect firm performance in the protected sector (Konings and Vandenbussche 2008, Pierce 2011, and Jabbour et al 2019, as well as employment (Trimarchi 2020, Cacciatore 2020, andBown et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Gallaway et al (1999) also evaluates the welfare loss from AD tariffs with a computable general equilibrium model. 8 Flaaen and Pierce (2019) and Trimarchi (2020) find that 2018-19 U.S. tariffs weakly increase employment in the protected sectors, but Barattieri and Cacciatore (2020) and Bown et al (2021) find that anti-dumping tariffs have insignificant employment effect on the protected sectors. Flaaen and Pierce (2019), Barattieri and Cacciatore (2020), and Bown et al (2021) find significant declines in employment in the downstream sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent papers have also focused on the adverse employment effects of tariffs but through temporary trade barriers on intermediate inputs. Bown et al (2021) find that US anti-dumping (AD) duties against China over the 1998-2016 period cost nearly 2 million jobs in downstream industries. Barattieri and Cacciatore (2020) find that employment in downstream industries falls by 0.5% points following a 1% point increase in the share of imports subject to AD and countervailing (CV) duties in upstream industries.…”
Section: Introductionmentioning
confidence: 99%